Автобіографічні спогади Григорія Світлицького - Новійчук, В. (Студії мистецтвознавчі, 2009)
Hryhoriy Svitlytsky (1872–1948) is a famous Ukrainian artist, teacher and musician. In the history of the Ukrainian Fine Arts he is known as an author of lyric landscape. His painting is inspired by musical impressions as music influenced all his creative works. The author offers a complete text of Svitlytsky’s memories named Colours and Sounds, Sounds and Colours. Svitlytsky recollects his studying at Murashko’s drawing school, meeting outstanding artists at the end of the 19th and beginning of the 20th centuries, notably M. Vrubel, I. Repin, A. Kuindzhi, O. Benua, М. Khuznetsov, P. Chystyakov.